2000
DOI: 10.1002/1097-0088(20001130)20:14<1729::aid-joc556>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Climatic warming in the Tibetan Plateau during recent decades

Abstract: Adequate knowledge of climatic change over the Tibetan Plateau (TP) with an average elevation of more than 4000 m above sea level (a.s.l.) has been insufficient for a long time owing to the lack of sufficient observational data. In the present study, monthly surface air temperature data were collected from almost every meteorological station on the TP since their establishment. There are 97 stations located above 2000 m a.s.l. on the TP; the longest records at five stations began before the 1930s, but most rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

67
1,015
7
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,547 publications
(1,098 citation statements)
references
References 33 publications
67
1,015
7
9
Order By: Relevance
“…Previous studies [Duan and Wu, 2006;Kang et al, 2007;Lin and Zhao, 1996; X. Liu and Chen, 2000;Niu et al, 2004] showed a significant warming in the TP during the last half century, in phase with the global trends derived from the increasing anthropogenic greenhouse gases emissions. The TP region is expected to be one of the most seriously impacted areas in the world by global warming effects [Chen et al, 2003;.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies [Duan and Wu, 2006;Kang et al, 2007;Lin and Zhao, 1996; X. Liu and Chen, 2000;Niu et al, 2004] showed a significant warming in the TP during the last half century, in phase with the global trends derived from the increasing anthropogenic greenhouse gases emissions. The TP region is expected to be one of the most seriously impacted areas in the world by global warming effects [Chen et al, 2003;.…”
Section: Introductionmentioning
confidence: 80%
“…During the past five decades, the QinghaieTibetan Plateau has experienced a universal and significant warming (Yao et al, 1997;Liu and Chen, 2000,;Duan et al, 2006;Li et al, 2010). The temperature has increased by 0.2 C per decade since 1960, with the warming trend even intensified since 2000 (Yao et al, 2007).…”
Section: The Fate Of Carbon Stored In Peatlands On the Qinghaietibetamentioning
confidence: 99%
“…Climate warming, land use changes and hydrologic redistribution have changed local, regional and global carbon cycle (Hicks Pries and Schuur, 2013) and have the potential to shift peatlands from a carbon sink to a carbon source (Dorrepaal et al, 2009;Knoblauch et al, 2013;Schuur et al, 2009;Wang et al, 2013;Yan et al, 2014). High altitude areas where climate is sensitive to warming are experiencing a "much larger than average" increase in temperature (Knoblauch et al, 2013;Lee et al, 2012;Liu and Chen, 2000;Peng et al, 2014). Besides warming, water table drawdown is the other very important cause for the degradation of peatlands in recent decades on Zoige Plateau peatlands -one of the largest alpine peatlands in the world (Bai et al, 2013;Chen et al, 2010;Gao, 2006;Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%